The Use of Intelligent Microprocessor Modules for Working with Sound Communication in the Development of Educational Equipment - Кartashov, Volodymyr; Tsekhmistro, Roman (Kharkiv National University of Radio Electronics, 2021)
This report is devoted to an overview of the technical characteristics and the specifics of the application of modern debugging microprocessor modules for recognizing audio and text signals.
Keywords: microcontroller system; RAM memory; EEPROM memory; RSC-4128 speech recognition processor